Impact of the SARS-CoV-2 pandemic on routine immunisation services: evidence of disruption and recovery from 170 countries and territories. Issue 2 (February 2022) - Shet, Anita; Carr, Kelly; Danovaro-Holliday, M Carolina; Sodha, Samir V; Prosperi, Christine; Wunderlich, Joshua; Wonodi, Chizoba; Reynolds, Heidi W; Mirza, Imran; Gacic-Dobo, Marta; O'Brien, Katherine L; Lindstrand, Ann
Summary: Background: The SARS-CoV-2 pandemic has revealed the vulnerability of immunisation systems worldwide, although the scale of these disruptions has not been described at a global level. This study aims to assess the impact of COVID-19 on routine immunisation using triangulated data from global, country-based, and individual-reported sources obtained during the pandemic period. Methods: This report synthesised data from 170 countries and territories. Data sources included administered vaccine-dose data from January to December, 2019, and January to December, 2020, WHO regional office reports, and a WHO-led pulse survey administered in April, 2020, and June, 2020. Results were expressed as frequencies and proportions of respondents or reporting countries. Data on vaccine doses administered were weighted by the population of surviving infants per country. Findings: A decline in the number of administered doses of diphtheria–pertussis–tetanus-containing vaccine (DTP3) and first dose of measles-containing vaccine (MCV1) in the first half of 2020 was noted. The lowest number of vaccine doses administered was observed in April, 2020, when 33% fewer DTP3 doses were administered globally, ranging from 9% in the WHO African region to 57% in the South-East Asia region. Recovery of vaccinations began by June, 2020, and continued into late 2020. WHO regional offices reported substantial disruption to routine vaccination sessions in April, 2020, related to interrupted vaccination demand and supply, including reduced availability of the health workforce. Pulse survey analysis revealed that 45 (69%) of 65 countries showed disruption in outreach services compared with 27 (44%) of 62 countries with disrupted fixed-post immunisation services. Interpretation: The marked magnitude and global scale of immunisation disruption evokes the dangers of vaccine-preventable disease outbreaks in the future. Trends indicating partial resumption of services highlight the urgent need for ongoing assessment of recovery, catch-up vaccination strategy implementation for vulnerable populations, and ensuring vaccine coverage equity and health system resilience. Funding: US Agency for International Development.